ÉTICA PROFESIONAL Y SU INCIDENCIA EN EL DESEMPEÑO LABORAL DE SECRETARIA EN LA PREFECTURA DE LOS RÍOS. - BURBANO MORALES MARÍA JOSÉ (2024)
Professional ethics plays a fundamental role in job performance, it is reflected in the behavior, integrity and responsibility of the secretariat in the exercise of its functions, contributing to improving the efficiency and effectiveness of the secretariat in its daily work. The research objective of this final project was to determine professional ethics and its impact on the work performance of the Secretariat in the Prefecture of Los Ríos. In this sense, a mixed descriptive and exploratory methodological approach was used, with a non-experimental, transversal design, where the study unit was made up of officials from the Prefecture of Los Ríos with a total of 17 to whom the survey was applied through a questionnaire with 11 questions on a Liker scale. In relation to the theoretical aspects and the results obtained, it has been concluded that there is a high level of professional ethics (61.22%) in relation to the good work performance of the secretariats; However, regarding the environment and performance evaluation process, they are not in line with the professional growth of the secretariats in the Prefecture of Los Ríos, since the lack of a system focused on obtaining results when evaluating employees is evident. officials, in the same way deficiencies in conflict resolution. Therefore, it is necessary to have a training program that covers all personnel based on compliance with professional ethics.